2023
DOI: 10.1021/acs.oprd.2c00348
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 1,2-Difluorobenzene via a Photochemical Fluorodediazoniation Step in a Continuous Flow Mode

Abstract: A proof-of-concept study for the synthesis of 1,2-difluorobenzene from 2-fluoroaniline via the Balz−Schiemann reaction using HF/pyridine as the fluorinating reagent is reported. Key to success for a fast reaction, a clean reaction profile�and thus high product selectivity�was a photochemically induced fluorodediazoniation of the in situ-generated diazonium salt performed in a continuous flow mode. A high-power 365 nm light-emitting diode provided a more robust and efficient irradiation system compared to a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The Balz-Schiemann reaction has been widely used in the synthesis of aryl fluorides but the harsh conditions and handling of potentially explosive aryl diazonium salts often hinder both the substrate scope and scalability. [67] In the previously mentioned works, Kappe has presented a mild and scalable photochemical Balz-Schiemann reaction in continuous flow while the aryl diazonium salt was generated in-situ. [66] Traditional batch Balz-Schiemann reactions require in-situ generation or isolation of aryl diazonium salts.…”
Section: The Balz-schiemann Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Balz-Schiemann reaction has been widely used in the synthesis of aryl fluorides but the harsh conditions and handling of potentially explosive aryl diazonium salts often hinder both the substrate scope and scalability. [67] In the previously mentioned works, Kappe has presented a mild and scalable photochemical Balz-Schiemann reaction in continuous flow while the aryl diazonium salt was generated in-situ. [66] Traditional batch Balz-Schiemann reactions require in-situ generation or isolation of aryl diazonium salts.…”
Section: The Balz-schiemann Reactionmentioning
confidence: 99%
“…Recently, Dallinger and Kappe reported the synthesis of 1,2difluorobenzene from 2-fluoroaniline via a flow photochemical Balz-Schiemann reaction. [67] The previously reported Balz-Schiemann route for the large-scale production of 1,2-difluorobenzene involved the decomposition of isolated and dried diazonium salts, which posed major safety risks due to their instability, [68] while further investigations revealed that a temperature of at least 150 °C was required. Although continuous flow can provide improved safety when applying extreme conditions, [22,69] pumping highly corrosive material at elevated temperatures and pressures still poses a challenge in operation.…”
Section: Flow Photochemical Fluorinationmentioning
confidence: 99%
“…According to statistics, the global demand for 2,4-dichloro-5-fluoroacetophenone is about 7000 tons, while the domestic demand for 2,4-dichloro-5-fluoroacetophenone in China is about 4000 tons. At present, o -dichlorobenzene is widely used as a raw material in industry to produce 2,4-dichloro-5-fluoroacetophenone through nitration, fluorination, nitrochlorination, and acetylation reactions. Although these four reactions are classical, there are still some shortcomings that need improvement in the actual production. The first reaction is to react nitrate o -dichlorobenzene with mixed acid, which will generate a large amount of waste acid and cause serious environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Other benefits are a confined reaction system and strong pressure resistance . Hence, it has the advantages of intrinsic safety, , precise control, and rapid scale-up. , It is well–known that these benefits have been demonstrated with good effect on fast and strong exothermic reactions, such as nitration and hydrogenation, , toxic and harmful reactions, such as chlorination and fluorination, dangerous and explosive reactions, such as azide oxidation and some extreme conditions. , Therefore, microreactor technology has been widely used in the fine chemical industry, life science and preparation of nanoparticles, and pharmaceutical continuous manufacturing, which are increasingly moving toward green and intelligent development …”
Section: Introductionmentioning
confidence: 99%